Reproductive Toxicity Induced by 5-Fluorouracil (5-FU) and the Potential Ameliorative Effects of Naringin in -28 Days Experimental Study in Wistar Rats - Sravathi Vemula; Jeevanalatha Mylaram; Swathi Bora; Nagarjuna Gandham; Mounika Kamishetti; Durga Veera Hanuman Donga; Bhaskar Debbarma (The Indian Veterinary Journal, 2024)
This study evaluates the potential ameliorative effects of Naringenin (NG) on testicular function in a 5-Fluorouracil (5-FU) induced testicular toxicity model. Male rats were divided into control, 5-FU treated, NG treated and NG + 5-FU combination groups with 6 animals each. Hormonal assays revealed a significant decrease in 5-FU treated group. Furthermore, pro-inflammatory cytokines (TNF-α, IL-1β, IL-6) exhibited a marked increase in the 5-FU group, which was significantly attenuated by decrease pro-inflammatory levels in NG + 5-FU combination group. Anti-inflammatory cytokine (IL-10) levels significantly decreased in 5-FU group but were notably restored with NG treatment along with hormone levels by mitigating chemotherapy-induced testicular damage.